Rainfall Characteristics In Medan City With Pearson Correlation Analysis (Case Study Of February 27, 2022) - Paramita, Endah; Humaidi, Syahrul; Darmawan, Yahya (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2023)
February is climatologically the first peak of the dry season in the North Sumatra region, but floods can still occur. This study analyzes the characteristics of rainfall patterns that occur during extreme rainfall that occurred in the Medan area on February 27, 2022 which resulted in flooding in several areas in Medan with Pearson correlation. The data used are rainfall data, satellite data, radar and other atmospheric dynamics analysis data. Based on dynamic analysis on February 27, 2022, the growth of CB clouds began at 14.00 WIB reaching its peak at 17.00 WIB where the peak temperature of the cloud reached 82.4 Â° C and cloud growth lasted until 21.00 WIB, where the rain lasted long enough to cause hydrometeorological disasters (floods) to occur. The Pearson correlation coefficient method (r) used to analyze the relationship between rainfall and DMI, ENSO, SST Anomalies and SOI conditions can be seen that the dominant influence is SST Anomalies and SOI, where in February conditions that affect rainfall are ENSO with a correlation value of 0.36272 and SST Anomalies with a correlation value of 0.37548.